3D geological model reconstruction and collapse risk evaluation of old goaf in Dunqiu iron mine - Hailong Wang; Zhenhua Zhao; Lin Han; Zhenjiang Luo (Scientific Reports)
Abstract The complexity of goafs put forward higher requirements for detection methods. A comprehensive detection method for old goaf is proposed, that is, determining the plane distribution range of old goaf by using high-precision magnetic method, determining the horizon of old goaf by using natural source surface wave method and controlled source audio magneto telluric method, and modifying the geophysical exploration results by using engineering drilling. Taking the old goaf of Dunqiu iron mine of China as an engineering background, the comprehensive detection method is successfully applied. The plane areas of goaf formed by mining of No. 1–3 orebody groups are 8640.6 m2, 4992.5 m2 and 6740.4 m2 respectively. The goaf can be divided into pure goaf and backfill goaf, which is 1–7 layers, 30.2–115.0 m buried depth, and 1.6–271.3 m mining thickness. A 3D geological model is constructed for displaying the situation of goaf visually. The goaf volumes of No. 1–3 orebody groups are 159,187.13 m3, 125,604.57 m3 and 174,435.28 m3 respectively. The stability of old goaf is evaluated by using two methods: influence depth of critical load and depth-thickness ratio of goaf, which is poor and has a risk of collapse. The detection method and results have certain guiding significance for the detection and treatment of old goaf in iron mine.